Study on Temperature Feedback Effect of Supercritical CO2–Cooled Reactor - Wang, Lianjie; Lu, Di; Yao, Lei; Xiang, Hongzhi; Zhao, Chen (Frontiers in Energy Research, 2021)
As a potential new-type reactor, supercritical CO2 (S-CO2) cooled reactor has several advantages, such as simple system, high thermal efficiency, small size and light weight. Due to the poor neutronics moderation performance, S-CO2 cooled reactor shows the disadvantage of weak temperature feedback effect on reactivity. In this paper, the neutronics performance of the reactor is focused and the effects of temperature feedback on fuel, coolant and moderator are studied and the method to improve the temperature feedback of S-CO2 reactor is proposed.